The Influence of Principal Academic Supervision, Work Environment and Self-Efficacy on Teacher Performance - Rizqiani, Wiwit (Transpublika Publisher, 2025)
This research seeks to investigate how the supervision of academic principals, the atmosphere at work, and self-confidence affect the teaching quality in high schools located in the Ngaglik District. The study follows an ex-post facto design with a focus on quantitative analysis. The population of this study was 111 teachers in high schools in Ngaglik District. The determination of the research sample of 93 teachers used the simple random sampling technique. The classical assumption test was carried out by testing for normality, linearity, multicollinearity, and heteroscedasticity. The study revealed that principal’s academic supervision (X1), work environment (X2), and self-efficacy (X3) each had a positive and significant impact on teacher performance (Y). Academic supervision (X1) had a regression coefficient of 0.419, t = 5.949 > 1.580, with a significance value of 0.000 < 0.05. The work environment (X2) showed a coefficient of 0.345, t = 4.668 > 1.580, and significance of 0.000 < 0.05. Self-efficacy (X3) recorded the highest influence, with a coefficient of 0.460, t = 6.920 > 1.580, and a significance value of 0.000 < 0.05. Simultaneously, academic supervision (X1), work environment (X2), and self-efficacy (X3) collectively influenced teacher performance (Y) significantly, indicated by F = 17.537 > 4.04, significance = 0.000 < 0.05, and an R² value of 0.401.